IMPROVING THE FOURTH GRADE STUDENT’S VOCABULARY MASTERY THROUGH APPLYING VISUAL AUDITORY KINESTHETIC (VAK) AT SDN 53 LUBUKLINGGAU - Fittrizah Listiani; Mulyadi; Hanni Yukamana (Universitas PGRI Palembang, 2024)
The focus of this classroom action research project is to find out how well fourth-grade children at SDN 53 Lubuklinggau comprehend vocabulary by using the Visual Auditory Kinesthetic (VAK) technique. The project intends to improve language acquisition in the classroom by using kinesthetic, auditory, and visual learning methods. This project aims to provide important insights into improving vocabulary education for students in primary schools using a methodical action research approach. It is anticipated that the results will have applications for teachers and curriculum designers who want to create dynamic and captivating language learning environments.